2022
DOI: 10.1007/s00422-022-00936-7
|View full text |Cite
|
Sign up to set email alerts
|

Auditory cortex modelled as a dynamical network of oscillators: understanding event-related fields and their adaptation

Abstract: Adaptation, the reduction of neuronal responses by repetitive stimulation, is a ubiquitous feature of auditory cortex (AC). It is not clear what causes adaptation, but short-term synaptic depression (STSD) is a potential candidate for the underlying mechanism. In such a case, adaptation can be directly linked with the way AC produces context-sensitive responses such as mismatch negativity and stimulus-specific adaptation observed on the single-unit level. We examined this hypothesis via a computational model b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 108 publications
1
17
0
Order By: Relevance
“…Thus, even if STSD dynamics and cortical folding are identical across hemispheres, differences in adaptation lifetime could arise via differences in connection pattern and strengths. Hajizadeh et al (2022) found that by changing which AC fields were connected to each other, i.e. by changing the connection pattern , the adaptation lifetime τ SOI was modified from 2.3 s to 2.7 s. The effect was thus of the same magnitude as observed in the current study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, even if STSD dynamics and cortical folding are identical across hemispheres, differences in adaptation lifetime could arise via differences in connection pattern and strengths. Hajizadeh et al (2022) found that by changing which AC fields were connected to each other, i.e. by changing the connection pattern , the adaptation lifetime τ SOI was modified from 2.3 s to 2.7 s. The effect was thus of the same magnitude as observed in the current study.…”
Section: Discussionsupporting
confidence: 76%
“…Figures 1c and d illustrate, as an example, the N1m-peak amplitudes from Figures 1a and b as a function of SOI for the left hemisphere (closed symbols) and the right hemisphere (open symbols). This relationship can be well approximated by a single saturating exponential function (Hajizadeh et al, 2022; Lu et al, 1992): …”
Section: Methodsmentioning
confidence: 99%
“…Studies based on the Human Neocortical Neurosolver (Kohl et al, 2022; Neymotin et al, 2020) suggest that the P1 and P2 components are partly generated by upward currents within the dendrites of cortical pyramidal neurons due to bottom-up inputs, while the N1 component is partly generated by downward currents associated with top-down inputs. Studies using a multi-column model of the auditory cortex (Hajizadeh et al, 2019, 2021, 2022) further emphasize the dependence of current orientation on the cellular location of the active synapses (e.g., apical/somatic), synaptic type (i.e., excitatory/inhibitory), inter-column connection type (e.g., feedforward, feedback, within-field), and folding of the cortex (i.e., the neuroanatomical topography of the cortical surface). At the level of a cortical column, our analyses of the cell-specific contributions to ECDs (Figure 7A) suggests that initial thalamic input primarily contributes to P1, subsequent early activity of E and PV neurons (both BF and non-BF columns) primarily contributes to N1, and late SOM activity (especially in non-BF columns) joins the contribution to P2.…”
Section: Discussionmentioning
confidence: 99%
“…This single-column model relates the ERP/ERF to intracellular currents in pyramidal long dendrites but leaves the origins of the sequences of inputs unexplained. This issue was addressed by a rate-based core-belt-parabelt model that includes an entire network of brain regions comprising auditory cortex (208 cortical columns, each column consisting of one excitatory and one inhibitory population), where ERFs are considered as the weighted sum of spatially distributed damped harmonic oscillators emerging out of coupled excitation and inhibition (Hajizadeh et al, 2019(Hajizadeh et al, , 2021(Hajizadeh et al, , 2022. This model provides a holistic perspective on the generation of ERFs.…”
Section: Existing Biological Modelsmentioning
confidence: 99%
See 1 more Smart Citation